2015
DOI: 10.1136/archdischild-2014-307843
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal factors modulate hearing screen failure risk in preterm infants

Abstract: Intrauterine infection with a fetal inflammatory response is a risk factor for neonatal hearing loss while maternal therapies significantly reduced the risk of neonatal hearing loss in very low birthweight infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 39 publications
(38 reference statements)
5
27
2
Order By: Relevance
“…In addition, funisitis also tended to be associated with increased incidence of SNHL in univariate analysis, although this trend did not reach the level of statistical significance. These findings are in line with the results of a previous report 15 and are to be expected given the strong association between severity of fetal vasculitis and multiple neurodevelopmental impairments (including hearing loss), which can be anticipated to cause significant SNHL, in extremely preterm infants. 27 Similarly, with regards to markers of systemic inflammation in the fetus other than funisitis, Leung et al 15 reported that elevated interleukin-6 (IL-6) level in cord blood, but not IL-1b and tumor necrosis factor level, was significantly associated with an increased risk of hearing screen failure.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, funisitis also tended to be associated with increased incidence of SNHL in univariate analysis, although this trend did not reach the level of statistical significance. These findings are in line with the results of a previous report 15 and are to be expected given the strong association between severity of fetal vasculitis and multiple neurodevelopmental impairments (including hearing loss), which can be anticipated to cause significant SNHL, in extremely preterm infants. 27 Similarly, with regards to markers of systemic inflammation in the fetus other than funisitis, Leung et al 15 reported that elevated interleukin-6 (IL-6) level in cord blood, but not IL-1b and tumor necrosis factor level, was significantly associated with an increased risk of hearing screen failure.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, our findings confirm the lack of association between histologic chorioamnionitis and either "refer" on the NHS test or SNHL shown in other studies. 12,15 We also found no association between clinical chorioamnionitis and abnormal hearing test results. These findings are consistent with the results of Pappas et al, 16 who demonstrated that infants exposed to histological and clinical chorioamnionitis were not at a Data are presented as mean AE standard deviation or n (%).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The initial sample size calculation was based on the previous study reporting the incidence of failure in the NHS test for preterm singletons to be 16%, 22 with an alpha of 0.05 and a power of 0.8. Assuming a ratio of 2:1 of preterm singletons to twins, we retrospectively calculated that a total sample size of 477 would be needed to detect an 11% difference in the incidence of "refer" results on the NHS test between preterm twins and singletons.…”
Section: Methodsmentioning
confidence: 99%
“…1 This is attributed to special problem among neonates, especially congenital anomalies, respiratory tract infections, acute diarrhoeal diseases and skin infections. 2 The increased rate of infections is due to immature immune system and poor functions of integumentary system when compared to those functions in the adults. However, these functions are even more impaired especially in the preterm infants.…”
Section: Introductionmentioning
confidence: 99%